THE EFFECT OF TEACHER’S COMPETENCE ON THE VOCATIONAL HIGH SCHOOL TEACHERS’ WORK SATISFACTION AND PERFORMANCE IN PRAJNAMITRA MAITREYA FOUNDATION, RIAU - Tohan Tohan; Nyoto Nyoto; Teddy Chandra (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
Education has a strategic function to achieve the national goals of the Indonesian nation as stated in the Preamble to the 1945 Constitution. Schools as the institutions that provide formal education need to ensure the quality of education offered by all teachers. Teachers as professional educators are at the forefront of a school. Schools continue to strive to improve the quality of education and services, by focusing on job satisfaction and improving teacher performance in order to provide the best quality education and services to students. This study aims to analyze the effect of pedagogic competence, personality competence, social competence, professional competence on job satisfaction and performance of vocational school teachers at the Prajnamitra Maitreya Foundation, Riau. The number of samples in this study was 55 teachers. The analysis used in this research is descriptive analysis and hypothesis analysis with path analysis. By using Smart PLS (Partial Least Squares), this study proves that personality competence has a positive and significant effect on teacher job satisfaction. Pedagogic competence, social competence, and professional competence have a positive and insignificant effect on job satisfaction. Personal competence and professional competence also have a positive and insignificant effect on teacher performance Pedagogic competence, social competence, and job satisfaction have a negative and insignificant effect on teacher performance.